Analisis Perbandingan Kontribusi Pajak Daerah terhadap Pajak Asli Daerah di Kota Samarinda dan Kota Balikpapan - Nina Maharani, Andi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the comparative contribution of regional taxes to local taxes in Samarinda City and Balikpapan City. By using secondary data from regional financial reports and income statistics, this research identifies factors that influence regional tax contributions and their impact on local original income (PAD). The research results show that there is a significant difference in the contribution of local taxes to PAD between Samarinda City and Balikpapan City. The city of Balikpapan shows a better contribution thanks to its natural resource potential and more active economic activities. To increase local tax contributions in Samarinda, efforts are needed to increase taxpayer compliance and improve infrastructure. Apart from that, collaboration between local governments and the community in increasing awareness of the importance of taxes is also very necessary.